8-Hydroxygenistein formation of soybean fermented with Aspergillus oryzae BCC 3088 - Chirtchai Punjaisee (2018)
The isoflavone content of soybean was studied by incubated Thai native soybean (Glycine max (L) Merr, SJ.2) with Aspergillus oryzae BCC 3088. The changes of the isoflavone analogue content were analysed by HPLC. Mass spectrometry was used to confirm the presence of substances in fermented soybean with the authentic standards. After fermentation, total glycosides content of soybean fermented with A. oryzae BCC 3088 decreased but the proportion of aglycone markedly increased. As for the increases of isoflavone aglycone during the fermentation, the proportion of aglycones in total isoflavones was markedly higher in soybeans fermented with A. oryzae BCC 3088 than was those from uninoculated soybean. Furthermore, 8-hydroxygenistein (8-OHG) was found at the fourth day of fermentation. Therefore, fermentation of soybean with A. oryzae BCC 3088 results in higher levels of isoflavone aglycones and their corresponding, 8-OHG, which may enhance more health benefits than unprocessed soybean. © 2011 Academic Journals.